Fractional crystallization for wastewater treatment from food industries: effect of operation time and solution concentration: article - Osman, Mohd Firdhaus; Ab Hamid, Farah Hanim (2018)
Fractional crystallization is a process where the water component in a solution is frozen and crystallized as ice so that the more concentrated solution will be left behind. This process is used to recover the water component in the waste solution from food industries during the wastewater treatment. The experiments were carried out to examine the effect of operation time and solution concentration on fractional crystallization process for the wastewater treatment. The performance analysis was executed by using glucose solution as simulated wastewater and was evaluated by the value of effective partition constant, K and percentage of water recovery, Rw. Operation time studied was recorded optimum efficiency at 15 minutes with high purity of ice formed, lowest Kvalue of 0.49 and highest water recovery of 42%. 1mg/ml showed the optimum concentration for solution concentration studied with the best separation efficiency. It was recorded the lowest K-value of 0.271.